Compliance with smoke-free laws in hospitality venues in Ethiopia: A cross-sectional observational study in 10 cities. - Wakgari Deressa; Selamawit Hirpa; Terefe Gelibo Argefa; Yifokire Tefera; Selam Abraham Kassa; Rachel Kitonyo-Devotsu; Winnie Awuor; Baharu Zewdie; Noreen Dadirai Mdege (PLoS ONE)
Background The 2019 Ethiopia's comprehensive tobacco control proclamation mandates 100% smoke-free public places and workplaces. Despite the proclamation, compliance remains uncertain, particularly at hospitality venues (HVs). The aim of this study was to evaluate the extent of compliance with smoke-free laws in HVs and to also understand the factors associated with non-compliance. Methods This cross-sectional observational study was conducted in 10 cities in Ethiopia-Addis Ababa, Adama, Assosa, Bahir Dar, Dire Dawa, Gambella, Harar, Hawassa, Jigjiga, and Semera-Logia -between December 5th and 28th, 2022. Data were collected electronically using smartphones, utilizing a pre-tested, standardized checklist and covert observation. The subjects were selected through multi-stage cluster sampling. A total of 1,370 HVs (hotels, restaurants, bars, bars and restaurants, café and restaurants, butcher houses and restaurants, groceries, and nightclubs/ lounges) were observed. Specific and composite compliance indicators were computed for indoor and outdoor spaces. Poisson regression analyses identified factors associated with indoor active smoking and non-compliance. Statistical significance was set at P<0.05. Data were analyzed using SPSS version 26. Results Among the 1,370 HVs included in this study, 1,368 had indoor spaces, 327 had both indoor and outdoor spaces, and two had only outdoor spaces. Active smoking was observed in 32.2% (95% CI:30-35) of indoor HVs, with the highest rates in nightclubs/lounges (68.6%) and bars (65.7%). Semera-Logia reported the highest prevalence of active smoking (70.4%). Adherence with 'no smoking' signage was low (35.2%), while ashtrays, lighters, and designated smoking areas (DSAs) were rarely present. Outdoor active smoking was observed in 46.5% (95% CI:41-52) of HVs. Only 12.8% of indoor spaces were fully adherent to the smoke-free law requirements. Venues in Semera-Logia were over twice as likely to have active smoking (adjusted prevalence ratio [aPR]: 2.71; 95% CI: 2.00-3.66) compared to Addis Ababa. Bars and nightclubs/lounges had significantly higher prevalence of active smoking than cafés/restaurants. 'No smoking' signs were associated with reduced prevalence of indoor active smoking (aPR: 0.77; 95% CI: 0.67-0.89), while smoking within a 10-meter range (aPR: 2.67; 95% CI: 2.13-3.32), the presence of lighters (aPR: 1.69; 95% CI: 1.41-2.02), and the sale of tobacco products (aPR: 1.58; 95% CI: 1.34-1.86) were all associated with higher prevalence of indoor active smoking. Conclusion Compliance with 'no active smoking' and adherence to smoke-free laws in HVs remain low, particularly in bars, nightclubs/lounges, and Semera-Logia, with high rates of active smoking both indoors and outdoors. Enhanced enforcement and targeted are needed to educate the public and HV owners about the risks of SHS and the importance of tobacco control laws.